Sputum Streptococcus pneumoniae is reduced in COPD following treatment with benralizumab - George L; Wright A; Mistry V; Sutcliffe A; Chachi L; Haldar K; Ramsheh MY; Richardson M; van der Merwe R; Martin U; Newbold P; Brightling CE (International Journal of COPD, 2019)
Leena George,1 Adam Wright,1 Vijay Mistry,1 Amanda Sutcliffe,1 Latifa Chachi,1 Koirobi Haldar,1 Mohammadali Yavari Ramsheh,1 Matthew Richardson,1 René van der Merwe,2 Ubaldo Martin,3 Paul Newbold,3 Christopher E Brightling11Department of Respiratory Sciences, Institute for Lung Health, National Institute for Health Research Biomedical Research Centre, University of Leicester, Leicester, UK; 2Clinical Respiratory Management, MedImmune Ltd., Cambridge, UK; 3Global Medical Affairs, AstraZeneca, Gaithersburg, MD, USAAbstract: We hypothesized whether the reduction in eosinophilic airway inflammation in patients with chronic obstructive pulmonary disease (COPD) following treatment with benralizumab, a humanized, afucosylated, monoclonal antibody that binds to interleukin-5 receptor α, increases the airway bacterial load. Analysis of sputum samples of COPD patients participating in a Phase II trial of benralizumab indicated that sputum 16S rDNA load and Streptococcus pneumoniae were reduced following treatment with benralizumab. However, in vitro, eosinophils did not affect the killing of the common airway pathogens S. pneumoniae or Haemophilus influenzae. Thus, benralizumab may have an indirect effect upon airway bacterial load.Keywords: COPD, benralizumab, IL-5, bacterial load, S. pneumoniae, H. influenzae